Islamic law of inheritance and its implication amongst Muslim society : an empirical analysis - Saujan, Iqbal; Mohamed Mahazir, Seyed Mohamed; Muhammadu Ibrahim, Nasrin (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2022)
Islamic inheritance law (Al-Fara'id) is a refined and commanded law by Almighty Allah. Almighty had reserved and held the right of legislative power on his control as he has commanded the people to implement the law of Inheritance bestowed by him. However, it is seen as a divine mandate that is being continually ignored by the Muslim community. Because the statute was not executed in accordance with the commends of the Almighty, it has caused plenty of socio-economic problems. In this background, this study aims to find out the reasons as to why the Islamic inheritance law has not been implemented properly among the Muslim community in Sri Lanka especially in Palamunai area densely populated with Muslims and to identify the obstacles and the reasons of present backward on implementing such law. The primary and secondary data have been utilized in this mixed-method study. It uses primary data collection techniques such as questionnaire (self-administrative), interviews and observations. The data collected were subjected to descriptive analysis with the help of SPSS software (Version-26). The results have been illustrated by graphs and charts Moreover, secondary data sources such as research articles, books, journals, web publications, etc. were used for the purpose of developing a theoretical framework on Islamic inheritance law. The findings of the study are: Dividing the property which is carried out after the death of the owner of the property with the own decision of inheritors and ignoring the divine commands where women are given first place in the quota with more shares and men are marginalized. The study reveals that the reasons of such conditions are the lack of awareness among the people of the area on Islamic Inheritance law and the nature of careless of the people who have awareness on implementing such law. The situations descried above would have led to impress the inappropriate concept and practices such as individual economy and the economy stipulated in the religion are different process in the practical life. The attraction and the social status given by the community for the dowry which is an economical deal of the marriage become stronger than the past. The researchers expect that this study would be helpful for future scholars and policy-makers to take suitable measures for implementing the Islamic inheritance law in the society.